Pengaruh Pengembangan Karir terhadap Kepuasan Kerja yang di Mediasi oleh Motivasi Kerja - Erina Rulianti; Mega Nurlilah (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
The purpose of this study is to determine whether there is an effect of career development on job satisfaction mediated by work motivation. The object of research at PT Tenma Indonesia Surya Cipta Karawang Industrial Estate. The research was conducted using quantitative methods with SEM Smart PLS software as an analysis tool. The number of samples obtained by sampling technique with saturated samples amounted to 92 respondents. Data collection was carried out using Google Forms in filling out online surveys. The data analysis method used is the R-square test, Bootstrapping, Path Coefficient, and Specific indirect effects. The results of this study indicate that career development has an effect on job satisfaction, career development has a positive and significant influence on work motivation, work motivation has a positive and significant effect on job satisfaction, work motivation can have a positive influence in mediating the relationship between career development and job satisfaction in employees. PT Tenma Indonesia.